Mining Wealth, Regional Inequality and Financial Exclusion in Central Africa: A Spatial Paradox within the CEEAC Region - (:unkn) unknown (My University, 2025)
Despite abundant mineral resources, many Central African regions remain financially underserved. This paper investigates the inclusion paradox in rentier economies within the CEEAC, showing that mining-rich areas—especially in the Democratic Republic of Congo—experience structural financial exclusion. Using a spatial econometric approach and geo-referenced data, we develop an Inclusion Paradox Index (IPI) to assess the link between extractive resource density and access to financial services. Results reveal a significant negative correlation between mineral wealth and financial inclusion. LISA cluster analysis and ArcGIS maps highlight persistent exclusion traps in cities like Kolwezi and Mbuji-Mayi. These findings call for a spatially redistributive approach to financial infrastructure and stronger local governance to overcome the resource-finance disconnect.
Keywords: African Research